“EVERYTHING ABOUT US IS FEMINIST”: The Significance of Ideology in Organizational Change - Thomas, Jan E. (Gender & Society, 1999)
This study explores the role feminist ideology played in long-term structural changes in feminist organizations. The vehicle for this exploration was a comparative case study of 14 feminist women's health centers that were started in the 1970s and were still in existence in the early 1990s. Drawing on interviews and site visits, the author describes the early collectivist structures, highlights some of the crises these organizations faced, and describes three structural ideal types that emerged in the 1990s. The analysis suggests three ideological issues that directed structural change: the importance of maintaining a system for the equitable distribution of power, the importance of growth versus autonomy, and the importance of feminism as an organizational outcome or internal process.
Keywords: 1900-1999; 1970-1979; 1980-1989; 1990-1999; amériques; approches et analyses; cours; cycles supérieurs; discipline; fem7000; justice sociale; militance; organisations féministes; pratiques féministes; périodes historiques; recherche participative; régions géographiques; sciences humaines; structures organisationnelles; thématiques; travail social; états-unis; étude de cas

Femmes, action politique et identité - Sève, Micheline de (Cahiers de recherche sociologique, 1994)
Centré sur la différence de genre, le mouvement des femmes serait condamné à l’éclatement à mesure que les femmes échappent à leur cantonnement dans l’appartenance à une catégorie sociale opprimée pour gagner l’espace qu’offre une société démocratique égalitaire à l’expression pluraliste des composantes multiples de leur personnalité publique. Une approche phénoménologique, axée sur la valorisation des expériences de vie et de l’histoire partagées de femmes se réclamant d’une culture civique commune, permet à l’autrice d’espérer dégager une stratégie féministe parallèle fondée sur la prise en compte des positions variées de sujets-femmes en situation pour les rallier autour d’actions politiques à mener en commun.
Keywords: cours; cycles supérieurs; discipline; fem9000; genre; identités LGBTQIA2+; militance; mouvements des femmes*; ressource en ligne; science politique; science politique et droit; thématiques

Mapping the margins: Intersectionality, identity politics, and violence against women of color - Crenshaw, Kimberlé William (Stanford Law Review, 1991)
Contemporary feminist and antiracist discourses have failed to consider the intersections of racism and patriarchy. To overcome this difficulty, an original approach is suggested here: that of intersectionality. In the first part, the paper discusses structural intersectionality, the ways in which the location of women of color at the intersection of race and gender makes their real experience of domestic violence, rape, and remedial reform qualitatively different from that of white women. The focus is shifted in the second part to political intersectionality, with the analysis of how both feminist and antiracist politics have functioned in tandem to marginalize the issue of violence against women of color. Finally, the implications of the intersectional approach are addressed within the broader scope of contemporary identity politics.
Keywords: 1900-1999; OFDIG; afro-féminisme; amériques; antiracisme; approches et analyses; cours; cycles supérieurs; fem9000; femmes* afro-américaines; féminismes noirs; incontournable; intersectionnalité; militance; patriarcat; périodes historiques; racisme; ressource en ligne; régions géographiques; systèmes d'oppressions; thématiques; violences; violences contre les femmes*; violences raciales; états-unis